Russia in Transition: Coverage by American Newspapers in the 1990s: Geography, Ideology, and Emotion in the Narration of Political-Economic Change - West, Eric (Vdm Verlag, 2009)
Keywords: 1991-; Mass media; Political aspects; Politics and government; Russia (Federation); Foreign news; Russia (Federation); Russia (Federation); dept.egm; faculty_collection

And Life Is Changed Forever: Holocaust Childhoods Remembered - Glassner, Martin Ira; Krell, Robert; Holocaust Child Survivors of Connecticut (Landscapes of childhood, 2006)
Contains brief memoirs, some of which describe experiences in the Holocaust. Includes commentary by psychologist and child survivor Robert Krell. Partial contents:
Keywords: Biography; Holocaust, Jewish (1939-1945); Connecticut; History and criticism; Influence; Holocaust, Jewish (1939-1945); Jewish children in the Holocaust; Personal narratives; Personal narratives; Holocaust survivors; dept.egm; faculty_collection

All Possible Worlds: A History of Geographical Ideas - Martin, Geoffrey J. (Oxford University Press, 2005)
Keywords: Geography; History; dept.egm

The Role of Geographer and Natural Scientist Henri Francois Pittier (1857-1950) in the Evolution of Geography as a Science in Costa Rica - Yacher, Leon I. (Mellen studies in geography ; v. 12, 2004)
Keywords: Costa Rica; History; History; Geography; Influence; Geography; Latin America; Pittier, Henri, 1857-1950; award_winner; dept.egm

Plants - Avery, David F.; Smith, Dwight G.; Schultz, Marcia H. (Pearson Custom Publishing, 2003)
Keywords: Botany; Plants; dept.egm; faculty_collection

Raptors of the Pacific Northwest - Bosakowski, Thomas; Smith, Dwight G. (Frank Amato Publications, 2002)
Keywords: Birds of prey; Identification; Northwest, Pacific; Northwest, Pacific; Birds of prey; dept.egm; faculty_collection

Great Horned Owl - Smith, Dwight G. (Wild bird guides, 2002)
Keywords: Great horned owl; dept.egm; faculty_collection

Bibliography on Land-Locked States, Economic Development and International Law - Glassner, Martin Ira (M.E. Sharpe, 2001)
Keywords: Bibliography; Bibliography; Access to the sea (International law); Landlocked states; dept.egm; faculty_collection

Plant Life - Smith, Dwight G.; Avery, David F.; Schultz, Marcia H. (Southern Connecticut State University ; Pearson Custom Pub., 2000)
Keywords: Nomenclature; Plants; Plants; dept.egm; faculty_collection

Three new species of Jaltomata (Solanaceae) from Ancash, Peru - Mione, T.; Leiva G., S.; Yacher, L. (Novon, 2000)
Three new Jaltomata species from the department of Ancash, Peru, are described and illustrated. The three species are distinguished from others in the genus by features of the flowers, hairs, and leaves. Fruits of Jaltomata cajacayensis S. Leiva and Mione are gathered for consumption. Jaltomata lomana Mione and S. Leiva is known only from a single fog-dependent plant community, a lomas formation. Jaltomata yungayensis Mione and S. Leiva is widely distributed at high elevations.
Keywords: Jaltomata; Jaltomata cajacayensis; Jaltomata lomana; Jaltomata yungayensis; Magnoliophyta; Solanaceae; dept.egm

The lead project. An environmental instrumental analysis case study - Breslin, V.T.; Sañudo-Wilhelmy, S.A. (Journal of Chemical Education, 2001)
Keywords: dept.egm; peer-reviewed

Jaltomata andersonii (Solanaceae): A new species of Peru - Mione, T.; Leiva G., S.; Yacher, L. (Rhodora, 2004)
Jaltomata andersonii (Solanaceae), here named, is distributed on the western slope of the Andes, in the Departments of Ancash and Lima, Peru, from 2300 to 3400 m of elevation. This species differs from others of the genus by having an unarticulated axis connecting the flower to the plant where all others have both a peduncle and a pedicel. The following combination of features also characterize this species: the hairs of leaves and axes are gland-tipped; the petiole is no longer than 1 cm; the flowers are solitary; the corolla is broadly crateriform-rotate, purple, and up to 3.7 cm in diameter; and the filaments are extremely villous at their bases.
Keywords: Andes; Corolla; Flora of Peru; Jaltomata; Jaltomata andersonii; Magnoliophyta; Solanaceae; dept.egm; ⛔ No DOI found

Photojournal: Venezuela - Yacher, L. (Focus on Geography, 2007)
Keywords: South America; Venezuela; dept.egm; imagery

Photojournal: Turkmenistan - Yacher, L. (Focus on Geography, 2006)
Keywords: Asia; Eurasia; Turkmenistan; West Asia; dept.egm; geographical research

The Kyrgyz Republic's Liminal Media: assessing a journalistic rite of passage - Manzella, Joseph C; Yacher, Leon (Journalism Studies, 2005)
In the Western world, the Kyrgyz Republic has been depicted as a democratic success story. Indeed, unlike other Central Asia nation states, the Kyrgyz media appears on the surface relatively free. This paper examines the Kyrgyz press in the context of journalistic ideologies, and suggests that the republic's media is going through an important transitional phase, the central stage of a journalistic rite of passage. Part of that transitional process is an ongoing ideological tug-of-war that awaits resolution. It is suggested that such resolution may occur only when the press becomes economically self-sustaining. © 2005 Taylor & Francis Group, LLC.
Keywords: Journalistic Ideologies; Kyrgyz Media; Rite of Passage; dept.egm

Citrate-mediated increase in the uptake of weathered 2,2-bis(p-chlorophenyl)1,1-dichloroethylene residues by plants - White, Jason C; Kottler, Bennett D (Environmental Toxicology and Chemistry, 2002)
Experiments were conducted to determine the ability of citrate to enhance the plant uptake of weathered 2,2-bis(p-chlorophenyl)1,1-dichloroethylene (p, p′-DDE) from soil. Plots containing three rows of clover, mustard, hairy vetch, or rye grass were constructed in soils containing p, p′-DDE. On 11 occasions, the rows of each crop received water or sodium citrate (0.005 or 0.05 M). For each crop, there were significant reductions in p, p′-DDE concentration in the soil fractions (near root and rhizosphere) closely associated with the plant versus bulk soil. The roots of each crop accumulated 2 to 5 times more of the weathered contaminant (dry wt) than present in the bulk soil. Citrate (0.05 M) increased the concentration of p, p′-DDE in the roots of clover, mustard, and hairy vetch by 39% compared with vegetation that received water. In batch desorption studies, the release of weathered p, p′-DDE was significantly greater in the presence of 0.05 M citrate than in water. Citrate increased the extracted aqueous concentrations of five metal ions (Al, Fe, Ca, K, Mn) from soil by five- to 23-fold over distilled water. We hypothesize that citrate physically disrupts the soil through chelation of structural metal ions and release of bound humic material, facilitating p, p′-DDE availability and uptake by plants.
Keywords: 1,1 dichloro 2,2 bis(4 chlorophenyl)ethylene; Bioavailability; Biodegradation, Environmental; Brassica; Chelating Agents; Chelation; Citric Acid; Dichlorodiphenyl Dichloroethylene; Drug Interactions; Extraction; Humic Substances; Impurities; Insecticides; Ions; Metals; Organic compounds; Phytoremediation; Plants; Plants (botany); Secale cereale; Sequestration; Soil Pollutants; Soil fractions; Soil pollution; Tissue Distribution; Trifolium; Vegetation; Vicia; Vicia villosa; Water; aluminum; aqueous solution; article; bioavailability; biological uptake; bioremediation; calcium; chelation; citric acid; clover; concentration (parameters); dept.egm; desorption; iron; manganese; metal ion; nonhuman; phytoremediation; plant; plant root; potassium; priority journal; rhizosphere; rye; soil pollution; water

Influence of soil moisture on the sequestration of organic compounds in soil. - Kottler, Bennett D.; White, Jason C.; Kelsey, Jason W. (Chemosphere, 2001)
A study was conducted as a part of continuing investigation of the effect of soil moisture on the sequestration of organic compounds aged in the soil. Here, experiments focused on the effects of moisture changes within the soil before, during, and after contaminant addition. The extractability of aged (68 d) phenanthrene was greater from soil that had been subjected to wetting and drying cycles prior to solute addition as compared to soil initially maintained at constant moisture. The recovery of phenanthrene added to moist soil was increased relative to extractability from soil that was air-dried at the time of the contaminant addition. Repeated wetting and drying of soil after the addition of atrazine or phenanthrene resulted in decreased extractability of the compounds as compared to samples maintained at constant moisture. A method for rapidly sequestering contaminants is proposed and may be useful in limiting the time required for laboratory studies involving "aged" contaminants. These data build upon the findings of earlier work from our laboratory and indicate that changes in the moisture conditions of soil can affect the availability of sequestered contaminants possibly through alterations in the structure of the natural solid. © 2001 Elsevier Science Ltd.
Keywords: Aging; Atrazine; Bioavailability; Biological Availability; Extraction; Organic Chemicals; Phenanthrene; Phenanthrenes; Soil; Soil Pollutants; Water; article; atrazine; bioavailability; chemical structure; dept.egm; extraction; leaching; moisture; organic compound; phenanthrene; phenanthrene derivative; soil moisture; soil pollution; solid state; wetting-drying cycle

Lessons in managed destination competitiveness: the case of Foxwoods casino resort. - d'Hauteserre, Anne-Marie (Tourism Management, 2000)
Foxwoods, which started as a Binge gaming facility, has become the largest casino in the western world. It is one of the most competitive tourist destinations in the world and can teach a few lessons about managing competitiveness. The visionary entrepreneurial activity, strategic management decisions of its owners and the Mashantucket Pequots are the reasons for its existence and its success, not some circumstantial fluke. The Pequots understood the destination's potential initial advantage. They then sought to avoid that Foxwoods casino and resort slip into McGambling or wither in the face of increasing competition for the entertainment/leisure dollar in the eastern United States by modifying its market positioning. They are now nudging it toward a broadly diversified base of entertainment. All along they empowered their employees to support their clear mission for the resort. Part of their strategy is to transform southeastern Connecticut into a synergistic tourist destination for their and the region's benefit. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: Competitiveness; Connecticut; Foxwoods; Gam(bl)ing; Strategic planning; Tourist destination; United States; competitiveness; dept.egm; gambling; management practice; recreational activity; tourism economics

A land use model of the effects of eco-labeling in coffee markets - Heidkamp, Patrick; Hanink, Dean M.; Cromley, Robert G. (Annals of Regional Science, 2008)
International non-profit organizations have started to implement eco-labeling for credence attributes programs aimed to inform consumers about environmentally sound or “sustainable” production standards for various products. Using coffee labeled as “shade grown” or “bird friendly” as an example, this paper describes the impact such labeling programs may have on local land use patterns in coffee producing regions. Shade grown coffee farms should provide a variety of external benefits, including the preservation of biodiversity, carbon sequestration, the prevention of soil erosion and aquifer recharge. Those externalities, however, are not expected to have observable land use impacts unless they are capitalized in the coffee market. The prospect of market capitalization of externalities suggests the extension of the conventional von Thunen model to the calculation of social location rent. Using the maximization of social location rent as a criterion allows the externality effect to play a direct role in market-based land use allocation of land between eco-labeled shade grown coffee production and other activities.
Keywords: Aves; agricultural market; coffee; crop production; dept.egm; ecolabeling; land use; modeling

Offshore threats: Liquefied natural gas, terrorism, and environmental debate in Connecticut - Harrison, Blake (Annals of The Association of American Geographers, 2008)
Broadwater Energy is one of a number of recent proposals to construct a liquefied natural gas facility along the East Coast of the United States. The proposal calls for the construction of an import and regasification terminal in Long Island Sound, roughly halfway between the states of New York and Connecticut. First made public in 2004 by its sponsors, TransCanada and Shell, the Broadwater proposal has inspired opposition from a range of interest groups. An examination of the Broadwater debate with a focus on arguments made by Connecticut residents in the months leading up to the release in late 2006 of the proposal's Draft Environmental Impact Statement reveals explicit and implicit points of overlap between concerns about the facility's environmental impacts and concerns about its status as a potential terrorist target. Discussions about terrorism deployed in the Broadwater debate have initiated and informed a politics of scale through which themes common to environmental debates have been transformed. This transformation, in turn, highlights the discursive and material influence of terrorism in contemporary U.S. society. Concerns about terrorist attacks have been deployed by activists to enhance the strength of an otherwise environmental debate and, in the process, those concerns have developed the potential to shape land use policy in Long Island Sound. Key Words: environmentalism, liquefied natural gas, Long Island Sound, scale, terrorism.
Keywords: Connecticut; Environmentalism; Liquefied natural gas; Long Island Sound; North America; Scale; Terrorism; United States; container terminal; dept.egm; environmental impact; environmental policy; environmentalism; land use planning; liquefied natural gas; offshore engineering; terrorism

Five new species of jaltomata (solanaceae) from cajamarca, peru - Mione, Thomas; Leiva, G Segundo; Yacher, Leon (Novon, 2007)
Five new suffrutescent to shrubby Jaltomata Schlechtendal species (Solanaceae) of the department of Cajamarca, Peru, are described and illustrated, Jaltomata contumacensis S. Leiva & Mione has a light green, urceolate-tubular corolla and grows in the province of Contumazá between 2530 and 3000 m; J. lanata S. Leiva & Mione has a whitish purple to pale purple, short-tubular corolla and grows in the province of San Pablo between 1850 and 2400 m; J. leivae Mione has a red-violet, urceolate corolla containing red nectar and grows in the province of Contumazá between 2560 and 2650 m; J. oppositifolia S. Leiva & Mione bas a white, broadly infundibular to rotate corolla and grows in province Chota between 2250 and 3090 m; and J. yacheri Mione & S. Leiva has a blue-purple, urceolate corolla and grows in province Hualgayoc at 3460 m. The fruits of two of these species are eaten by people.
Keywords: Edible fruit; Jaltomata; Magnoliophyta; Red nectar; Solanaceae; dept.egm

Shopping to save: green consumerism and the struggle for northern Maine - Harrison, Blake (Cultural Geographies, 2006)
Between 2001 and 2003, Roxanne Quimby - then the sole owner of a natural personal-care products company named Burt's Bees - invested millions of dollars of her company's profits in tens of thousands of acres of forestland in northern Maine. Her intention was to donate that land to the United States government on behalf of a controversial national park proposed for the region - the Maine Woods National Park. Quimby's actions set off sharp debates between policy makers, environmentalists and residents of northern Maine. As this article suggests, those debates were informed in part by their association with green consumerism. When consumers purchase `environmentally friendly' products like those made by Burt's Bees, they typically envision their actions as having positive consequences for places associated directly with the production and consumption of that product. In this case, however, profits from a green consumer product were reinvested outside its immediate commodity chain, thereby implicating green-consumer decisions in a politics of identity and landscape control beyond that product's lifecycle. This paper explores that process, suggesting that even the most well-intended consumer choices can carry social and environmental consequences into new and perhaps unexpected terrain. When we shop to save, we can never be quite certain of what it is that we are saving.
Keywords: Apoidea; Maine; North America; United States; consumption behavior; dept.egm; profitability